American jewry: transcending the European experience? - Wiese, Christian; Wilhelm, Cornelia (Bloomsbury Academic, 2017)
Klappentext: This book explores new transnational questions in Jewish history, analyzing the historical, cultural and social experience of American Jewry from 1654 to the present day, and evaluates the relationship between European and American Jewish history. Did the hopes of Jewish immigrants to establish an independent American Judaism in a free and pluralistic country come to fruition? How did Jews in America define their relationship to the 'Old World' of Europe, both before and after the Holocaust? What are the religious, political and cultural challenges for American Jews in the twenty-first century? Internationally renowned scholars come together in this volume to present new research on how immigration from Western and Eastern Europe established a new and distinctively American Jewish identity that went beyond the traditions of Europe, yet remained attached in many ways to its European origins.